Optimization of TEC-cooled closed-end oscillating heat pipe charged with degassed, deionized water - De Castro, Leandro T.; De Leon, Rizalinda L. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
A three level, three factor Box-Behnken design of experiment was conducted to determine the optimum operating condition and the effects of heat load, fill ration and tilt-angle on the performance of a TEC-cooled oscillating heat pipe charged with degassed, deionized water. The fitted quadratic model for thermal resistance, device temperatures, and ΔT evaluated at quasi-steady state condition against heat load of 50 watts to 100 watts, fill ratio of 30% to 70% and tilt-angle of 30º to 60º were all significant (α=0.05). The three main effects were found to be significant in all response models except for the inclination angle having no significant effect on the average condenser temperature. Interaction of heat load and fill ratio has a negative effect on all the response variables while the quadric effect of fill ratio is high for the average evaporator temperature and ΔT. The minimum thermal resistance of 0.0838475 ΔºC/Watts and minimum evaporator temperature of 43.4ºC were obtained at 58.38 Watts heat load, 37.87% fill ration, and 90.00º tilt angle. The functional models obtained can be used as basis for comparison with variations of other parameters affecting OHP performa
Thesis (M.S. Chemical Engineering)--University of the Philippines Diliman
Keywords: Heat pi